Combined Laparoscopic and Hysteroscopic Management of Cesarean Scar Pregnancy: A Case Series - Rahim, Arooba; Siraj, Javaria; Khalid, Isma; Bhatti, Shehnaz Zulfiqar; Javaid, Mian Adnan Aslam (Biological and Clinical Sciences Research Journal, 2025)
Cesarean scar pregnancy (CSP) is an uncommon form of ectopic implantation associated with risks of severe hemorrhage, uterine rupture, and loss of fertility. With rising cesarean delivery rates, CSP is increasingly encountered, yet optimal management remains debated. A combined minimally invasive strategy—using hysteroscopic guidance for precise intrauterine resection and laparoscopic access for hemostasis and layered scar repair may enhance safety while preserving reproductive potential. Objective: To assess the safety and efficacy of a combined laparoscopic and hysteroscopic approach in managing cesarean scar ectopic pregnancies, focusing on surgical outcomes and complications in a series of eight cases. Methods: Eight patients with a cesarean scar pregnancy (CSP) diagnosed by transvaginal ultrasound were managed at our institution. Initial management (systemic methotrexate and/or ultrasound-guided intragestational injection in selected cases) was followed by a combined laparoscopy and hysteroscopy to remove gestational tissue and repair the uterine scar. Intraoperative blood loss, need for conversion to open surgery or additional interventions, and postoperative recovery were recorded. Results: All eight patients were successfully treated without conversion to laparotomy. Seven patients underwent fertility-preserving laparoscopic-hysteroscopic resection of the scar pregnancy, and one patient with life-threatening hemorrhage and completed childbearing underwent a laparoscopic hysterectomy. No severe intraoperative complications occurred; notably, none of the patients experienced uncontrolled hemorrhage, and there was no need for blood transfusion or reoperation in this series. Postoperative recovery was uneventful in all cases, with rapid decline of serum β-hCG and preservation of the uterus (in those desiring future fertility). Conclusion: A combined laparoscopic and hysteroscopic approach is a safe and effective therapeutic option for cesarean scar pregnancies. This minimally invasive technique allowed precise removal of the gestational sac and repair of the uterine defect with minimal blood loss and avoidance of open surgery. Our case series supports emerging evidence that operative resection (via laparoscopy with hysteroscopic guidance) offers high success rates with low morbidity, making it a valuable alternative to more invasive or medically-only management. Further larger studies are warranted to confirm these outcomes and guide standardized management for CSP.